Construção e validação de jogo cognitivo relacionado a temas afetivos para idosos - Nascimento, Wanessa Maria Silva do (2024)
Introduction: There is a growing concern about healthy and active old age. This is due to the phenomenon of population aging, which is increasingly progressive in society. To build successful aging, it is understood that the functional capacity or functionality of the elderly is based on an expanded concept of health, which understands that people are and do what they value. However, for the elderly to maintain functionality in their daily lives, the cognitive component is an essential factor, since problems of this nature contribute to the decline in functional capacity and quality of life. Objective: Build and validate a cognitive stimulation resource for the elderly that associates memory with affective themes. Method: This is a methodological study, consisting of a scoping review; development of a card game and content validation. The review was carried out based on the guiding question “What are the benefits attributed to games for cognitive stimulation, applied to the elderly?”, through research in databases about the resources used by occupational therapy for cognitive stimulation of elderly people. For the development of the product, data from the review were considered in the construction of a card game that addressed issues related to affective themes, which are part of the sociocultural context of the elderly. Content validation was carried out by expert judges (geriatricians, psychologists, speech therapists and occupational therapists), through a field study, applying the Content Validation Index (CVI). In addition to these, elderly people participating in activities in the Instituto Paraibano de Envelhecimento – IPE/UFPB and elderly patients admitted to the medical clinic at Hospital Universitário Lauro Wanderley HULW/UFPB. Results and Discussion: In the first stage, the scope review allowed allocating the results into 3 thematic categories: 1) intervention time; 2) game characteristics; and 3) benefits of using games for the elderly. In this way, it was possible to verify that the games used showed positive results in terms of stimulating cognitive components, especially those related to attention, memory, language and executive function. The use of games also demonstrated benefits in other areas of the elderly's life, with regard to social, psychological and personal aspects, influencing functionality and quality of life. Another benefit is that the cognitive gains resulting from the interventions remained for some time after the training ended. Based on the findings of the review, the construction of the card game began. The themes were arranged in different colors and illustrations and can be used by health professionals and family members, individually or in groups with managers. Final considerations: This study proved to be relevant, as it allowed expanding knowledge about what has been produced in the scientific world regarding the use of games for cognitive stimulation with the elderly. The results obtained in the study stages (review and validation) supported the construction of a cognitive game aimed at the elderly audience. The content validation stage was also essential to identify the details in this game construction process, qualifying it to stimulate cognitive components through affective memories.